Analysis of Factors Affecting User Satisfaction with Using the Quick Response Code Indonesian Standard (QRIS) Payment System - Muhammad Daffa Satria Meidi Prakosa; Anderes Gui (Syntax Idea)
Quick Response Indonesian Code (QRIS) is a new innovation that makes payments faster compared to other digital payments as it takes less than a minute to make a payment. Implementing QRIS has a reputation for making every transaction fast, easy and effective. Due to its effectiveness and ease of use, QRIS has exploded in popularity across Indonesia and across generations. This study explores which factors may influence user satisfaction when using the Quick Response Indonesia standard payment system. This research is expected to be a tool not only for QRIS service providers, but also to facilitate innovation in QRIS technology